The bright side of bank lobbying: Evidence from the corporate loan market - Delis, Manthos D.; Hasan, Iftekhar; To, Thomas Y.; Wu, Eliza (Journal of Corporate Finance, 2024)
Bank lobbying has a bitter taste in most forums, ringing the bell of preferential treatment of big banks from governments and regulators. Using corporate loan facilities and hand-matched information on bank lobbying from 1999 to 2017, we show that lobbying banks increase their borrowers' overall performance. This positive effect is stronger for opaque and credit-constrained borrowers, when the lobbying lender possesses valuable information on the borrower, and for borrowers with strong corporate governance. Our findings are consistent with the theory positing that lobbying can provide access to valuable lender-borrower information, resulting in improved efficiency in large firms' corporate financing.